(untitled) (Research, Society and Development, 2022)
The present research is characterized by the explorer’s interest in seeking quantitative data from the Reference Center for Assistance to Women (CRAM) in the year 2021. This space is intended to provide reception and humanized care to women who are in situations of violence, as well as, promoting social and psychological care, with guidance and legal referrals necessary to overcome violence, cooperating to strengthen women. For data collection, a quantitative documentary analysis of the anamnesis carried out by the CRAM Social Service team from January to December 2021 was carried out. physical violence by men, which demonstrates the great need for treatment and punishment for men who cannot manage their impulses and use physical, economic or psychological force to abuse women.